B. Britten’s “Guide to the Orchestra”: to the Question of the Unity of the Artistic and Pedagogical Aspects of the Composer’s Plan - Andrey M. Lesovichenko (Музыкальное искусство и образование, 2019)
The article presents an analysis of one of the most interesting orchestral compositions intended to familiarize listeners of symphonic concerts with instruments – compositions by Benjamin Britten “Guide to the orchestra. Variations on Purcell’s theme” The composer created his opus in such a way that it could be played in educational programs. At the same time, the composition has a great artistic value. This allows us to consider it in purely musical and pedagogical aspects. The problems of the variation cycle as a dynamically developing flow of diverse images are determined by intonation segments emanating from the theme borrowed from Henry Purcell, in which the initial idea of the master of the XVII century is deeply rethought. The pedagogical task is connected with the demonstration of the timbres of all instruments in solo, ensemble, orchestral sounds, expressing different semantic facets of the original theme, transformed in the process of development into its own antipode. B. Britten found an organic solution to the problems. The article outlines the options for the use of this work in music lessons in secondary school and in the system of additional musical education in the study of instruments of the Symphony orchestra. For this purpose, the comparative characteristics of the performance of the “Guide” by major conductors of different generations are involved, including the interpretation of the composition by the author of the music, which can be assessed a reference. The characteristic of the film for which the music and contemporary videos of the performance of Britten’s opus are written is given.